Sediment Characteristics and Prediction of Sediment Yield in Drainage Channel: A Study on Yos Sudarso Street Cikarang City - Irianto, Emilia Arista; Sudjatmiko, Eddy Triyanto; Bali, Ika (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2024)
Yos Sudarso Street, Cikarang City, is crucial for mobility and economic activity. However, Yos Sudarso Street has waterlogging and flooding issues due to severe sediment accumulation, resulting in siltation of the channel, so it cannot flow stormwater properly. This study aims to identify sediment characteristics and predict sediment yield in the drainage channel on Yos Sudarso Street, Cikarang City. It’s essential because sediment has negative impacts on drainage channels. The limited studies on sediment characteristics and sediment yield prediction in urban areas make this study necessary. The bed sediment samples were taken from 3 points in the drainage channel to identify the sediment characteristics. Sediment yield prediction using the Universal Soil Loss Equation method based on rainfall erosivity, soil erodibility, slope length, steepness, and crop management factors. The sediment characteristics at sites 1, 16, and 17 were dominated by large sand grains (0.82-1.81 mm) that were difficult to transport. Poorly sorted indicates low flow energy. Grain size distribution extends to fine grains. Sites 1 and 17 are concentrated at mean size, while site 16 is concentrated at the extreme size. The sediment yield prediction by the universal soil loss equation is 1.989 (t/ha/yr). This information can be used to formulate effective sedimentation control strategies.